Cholic acid-based novel micellar nanoplatform for delivering FDA-approved taxanes. (May 2017) - Bharadwaj, Gaurav; Nhan, Viet; Yang, ShanChao; Li, Xiaocen; Narayanan, Anand; Macarenco, Ana Carolina; Shi, Yu; Yang, Darrion; Vieira, Letícia Salvador; Xiao, Wenwu; Li, Yuanpei; Lam, Kit S
Aim: To structurally modify our existing cholic acid (CA)-based telodendrimer (TD; PEG 5K -CA8 ) for effective micellar nanoencapsulation and delivery of the US FDA-approved members of taxane family.Materials & methods: Generation of hybrid TDs was achieved by replacing four of the eight CAs with biocompatible organic moieties using solution-phase peptide synthesis. Drug loading was done using the standard evaporation method.Results: Hybrid TDs can generate micelles with narrow size distributions, low critical micelle concentration values (1–6 μM), better hematocompatibility and lack of in vitro cytotoxicity.Conclusion: Along with PEG 5K -CA8, CA-based hybrid nanoplatform is the first of its kind that can stably encapsulate all three FDA-approved taxanes with nearly 100% efficiency up to 20% (w/w) loading.